Original paperProspective multi-center dosimetry study of low-dose Iodine-125 prostate brachytherapy performed after transurethral resection - Salembier, Carl; Rijnders, Alex; Henry, Ann; Niehoff, Peter; Siebert, Frank André; Hoskin, Peter (Journal of Contemporary Brachytherapy, 2013)
Purpose : To evaluate in a multicenter setting the ability of centers to perform pre-implant permanent prostate brachytherapy planning, fulfilling dosimetric goals and constraints based on the Groupe de Curiethérapie-European Society for Radiotherapy and Oncology guidelines in the setting of implantation after prior prostate transurethral resection (TURP). Material and methods : A reference transrectal ultrasound image set of the prostate gland from a patient who had undergone TURP was used. Contouring of the prostate, clinical target volume and organs at risk was performed by the coordinating center. Goals and constraints regarding the dosimetry were defined. Results: Seventeen of twenty-five centers invited to participate were able to import the Digital Imaging and Communications in Medicine-images into their planning computer and plan the implant using the defined guidelines. All centers were able to plan treatment, and achieve the recommended objectives and constraints. However, sector analysis has shown a risk of under-dosage in the anterior part of the prostate. Conclusions : Correct pre-implantation planning with adherence to protocol guidelines and in compliance with defined dosimetric constraints seems feasible in a post-TURP setting, at least on a theoretical basis. A prospective study evaluating the outcome of prostate brachytherapy performed after TURP can therefore be undertaken with an expectation of a correct dosimetry in the multicenter setting.